Scutellarin Attenuates the IL-1β-Induced Inflammation in Mouse Chondrocytes and Prevents Osteoarthritic Progression - Zucheng Luo; Zucheng Luo; Zucheng Luo; Zhichao Hu; Zhichao Hu; Zhichao Hu; Yujie Bian; Yujie Bian; Yujie Bian; Wenting Su; Xiaoyang Li; Xiaoyang Li; et al. (Frontiers Media S.A., 2020)
Osteoarthritis (OA) is a chronic degenerative disease wherein the articular cartilage exhibits inflammation and degradation. Scutellarin (SCU) is a flavonoid glycoside with a range of pharmacological activities, as shown in previous studies demonstrating its anti-inflammatory activity. How SCU impacts the progression of OA, however, has not been explored to date. Herein, we assessed the impact of SCU on murine chondrocytes in an OA model system. In in vitro assays, we measured chondrocyte expression of key OA-associated factors such as matrix metalloproteinase 13 (MMP-13), a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) via qRT-PCR and Western blotting, the expression of interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α), and prostaglandin E2 (PGE2) were detected by qRT-PCR. Our results showed that the downregulation of MMP-13, ADAMTS-5, COX-2, and iNOS expression by SCU and the overproduction of IL-6, TNF-α, and PGE2 induced by IL-1β were all inhibited by SCU in a concentration-dependent manner. Moreover, SCU was able to reverse aggrecan and collagen II degradation and nuclear factor-κB (NF-κB) and nuclear factor erythroid-derived 2-like 2 (Nrf2) signaling pathway activation both in vivo and in vitro. We further used a destabilization of the medial meniscus (DMM) murine model of OA to explore the therapeutic benefits of SCU in vivo. Together, our findings suggest SCU to be a potentially valuable therapeutic agent useful for treating OA.